Canine-Assisted Interviews Bolster Informativeness for Negative Autobiographical Memories. Issue 1 (February 2020) - Capparelli, Amy L.; Miller, Quincy C.; Wright, Daniel B.; London, Kamala
Humans and animals share a unique bond. Professionals are capitalizing on the human–animal bond by incorporating animals into therapy, forensic interviews, and the courtroom. However, the mnemonic consequence for including dogs in forensic interviews has not been empirically evaluated. In the current study, we examined whether the use of dogs increases the quantity of verbal reports for emotional events. Undergraduate participants were randomly assigned to dog or no dog conditions. Participants were interviewed about positive experienced events and negative experienced events. All interviews were audio recorded, transcribed verbatim, and analyzed for quantity of new information. Participants shared more new information in negative event reports with a dog present than with no dog present. There were no significant differences in the quantity of information disclosed for positive event memories between dog conditions. Canine-assisted interviews may provide comfort to people, resulting in more elaborative autobiographical reports about negative stressful events.